Management of peri-implant infections - K L Vandana; Priyanka Dalvi; Disha Nagpal (Wolters Kluwer Medknow Publications, 2015)
The ever-increasing popularity of dental implants in recent years has been associated with the reported incidence of short-term and long-term complications such as peri-implant mucositis and peri-implantitis. Therapies proposed for treating peri-implantitis are based on the evidence available for the treatment of periodontitis, and are aimed at reducing the bacterial load within peri-implant pockets and decontaminating implant surfaces, and, in some cases, attempting afterward to bring about bone regeneration. The treatment of peri-implant infections comprises conservative (nonsurgical) and surgical approaches. This paper reviews various treatment strategies used for the treatment of peri-implant diseases. There are many approaches suggested by various authors for the treatment of peri-implant diseases, but there is no "ideal peri-implant therapy" that has been described in the literature. There is no consensus regarding the treatment protocol as the studies conducted so far have had varying study designs, small sample sizes, and short follow-up periods.